Plant cell cycle: cellularisation of the endoderm needs spatzle. - Dickinson, H (2003)
Early development of the endosperm of flowering plants involves the formation of a syncytium through successive rounds of nuclear division without cell wall synthesis. New data reveal that cellularisation of this syncytium requires the SPATZLE protein and involves the formation of cell walls similar to those of somatic tissues.